Visual Analysis of Totoro's Character in The Film My Neighbor Totoro - Rizkya, Luthufunnisa; Tarmawan, Irwan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Totoro in the film "My Neighbor Totoro" has become the most iconic character among other Studio Ghibli films. Studio Ghibli is a Japanese animation studio that has produced many legendary animated films. The company, which was founded in 1985, is led by Hayao Miyazaki, whose name is already very famous thanks to the success of his films. One of the animated films produced by Studio Ghibli is "My Neighbor Totoro". With a refreshing story and full of fantasy, Totoro in the film "My Neighbor Totoro" managed to grab the attention of the audience. Her large body and overgrown with cat-like fur and has a big smile that reveals teeth makes her look very adorable. The focus of this research is on the design and visualization of character characters. The purpose of this study is to describe how to design a character and how the visual character of the character is using a qualitative descriptive method using a research procedure in the form of presenting data with research that will be converted into writing. The character characters studied will be presented with design strategies, descriptions and visual analysis that include character design and expression. With the results of the research that has been carried out, this research can be a source of the latest reference materials, comparison materials, and others for animators and illustrators in making a character design.